A consensus on the Aquaporin Gene Family in the Allotetraploid Plant, Nicotiana tabacum. (7th May 2021) - Groszmann, Michael; De Rosa, Annamaria; Ahmed, Jahed; Chaumont, François; Evans, John R.
Abstract: Aquaporins (AQPs) are membrane‐spanning channel proteins with exciting applications for plant engineering and industrial applications. Translational outcomes will be improved by better understanding the extensive diversity of plant AQPs. However, AQP gene families are complex, making exhaustive identification difficult, especially in polyploid species. The allotetraploid species of Nicotiana tabacum (Nt; tobacco) plays a significant role in modern biological research and is closely related to several crops of economic interest, making it a valuable platform for AQP research. Recently, De Rosa et al., (2020) and Ahmed et al., (2020), concurrently reported on the AQP gene family in tobacco, establishing family sizes of 76 and 88 members, respectively. The discrepancy highlights the difficulties of characterizing large complex gene families. Here, we identify and resolve the differences between the two studies, clarify gene models, and yield a consolidated collection of 84 members that more accurately represents the complete NtAQP family. Importantly, this consensus NtAQP collection will reduce confusion and ambiguity that would inevitably arise from having two different descriptive studies and sets of NtAQP gene names. This report also serves as a case study, highlighting and discussing variables to be considered and refinements required to ensure comprehensive gene family characterizations, which become valuable resources for examining the evolution and biological functions of genes.